City; a story of Roman planning and construction. - Macaulay, David (Boston, Houghton Mifflin, 1974)
Text and black and white illustrations show how the Romans planned and constructed their cities for the people who lived within them.
Keywords: Civil engineering -- Rome -- Juvenile literature; Building -- Rome -- Juvenile literature; City planning -- Rome -- Juvenile literature; Civil engineering -- Rome; Building -- Rome; Rome -- Antiquities -- Juvenile literature; Rome -- Antiquities